VD_FINDINFO AI 87/12 - 113/2013 vom 25. März 2013 - VD Tribunal cantonal (2013)
DEGRÉ DE L'INVALIDITÉ, RÉVISIONDÉCISION, SITUATION FINANCIÈRE, COMPARAISON DES REVENUS | 28 al. 2 LAI, 31 al. 1 LAI, 4 al. 1 LAI, 17 LPGA, 25 al. 2 LPGA, 6 LPGA, 7 LPGA, 8 al. 1 LPGA